Архітектоніка лінгвального контенту в проєкті "Безкінечна подорож, або Енеїда" - Ганжа, А. (Культура слова, 2019)
У статті запропоновано авторську рецепцію мовної архітектоніки мультимедійного колажу «Безкінечна подорож, або Енеїда» (2017). Просторова організація макротексту медіапродукту проєктується на своєрідний діалог двох мовних особистостей і відповідно двох мовно-естетичних практик Івана Котляревського і Юрія Андруховича. Текстовий контент колажу потенційований оригінальним аудіовізуальним супроводом. Еклектичність новітніх культурних продуктів зумовлює відповідну організацію мовного матеріалу. The architectonics of the lingual content of the multimedia collage «Endless Journey, or Aeneid», aims to form a holistic view of the ideological content (content) of the cultural product. The spatial organization of the macrotext of the media product involves a kind of dialogue between two linguistic persons and, accordingly, two cultural and aesthetic practices of Ivan Kotlyarevskyi and Yurii Andrukhovych. Contemporary Ukrainian poet is seen in various communicative roles – scientist-philologist, writer-postmodernist, actorreader, epitaph philosopher-destroyer of stereotypes, and also in love with literature reader. The Father of New Ukrainian Literature communicates with the audience through quoted quotations from «Aeneid». The architecture of the lingual content under consideration is nonlinear, internal and external, verbal and non-verbal communication is involved. Text material of a media product potentiated by original audiovisual accompaniment. The cultural polycode “Endless Voyages, or Aeneids” is projected onto the public polylogue about the search for new ways and means of aesthetically comprehending reality in diachrony and synchronicity.